1997
DOI: 10.1023/a:1005822318256
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diet on mammary cancer in transgenic mice bearing an oncogene expressed in mammary tissue

Abstract: Breast cancer is one of the most common cancers in women. The laboratory rat treated with strong carcinogen is the most commonly used animal model for study of breast cancer. Transgenic mouse lines with homologues of human breast cancer oncogenes have been developed. The transgenic mouse line TG.NK with c-neu, the human breast cancer oncogene homologue of erbB2, was evaluated to determine its suitability for study of intervention strategies to delay/prevent the development of breast cancer. There were no palpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The NTP-2000 diet has been selected for the National Toxicology Program’s toxicology and carcinogenesis studies since 1995 (Rao et al, 1997). Soybean and fish meals are the major sources of protein, corn and wheat products are the major sources of carbohydrates, soy oil and corn oil are the major sources of fat, and alfalfa meal, oat hulls and purified cellulose are the major sources of fiber in this diet.…”
Section: Discussionmentioning
confidence: 99%
“…The NTP-2000 diet has been selected for the National Toxicology Program’s toxicology and carcinogenesis studies since 1995 (Rao et al, 1997). Soybean and fish meals are the major sources of protein, corn and wheat products are the major sources of carbohydrates, soy oil and corn oil are the major sources of fat, and alfalfa meal, oat hulls and purified cellulose are the major sources of fiber in this diet.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic founders were maintained, when not breeding, on the AIN 76A-Teklad-purified diet, with casein for protein, cornstarch and sucrose for carbohydrates, corn oil for fat, and purified cellulose for fiber, a diet shown to enhance mammary tumor formation in a previously published study (21).…”
Section: Methodsmentioning
confidence: 99%
“…The studies reported that the exposure reduced (Rao et al, 1997;Liu et al, 2005), increased (Thomsen et al, 2006), or had no effect (Day et al, 2001;Jin and MacDonald, 2002;Luijten et al, 2004) on mammary tumour incidence and/or multiplicity and size. In addition, a delayed tumour onset after genistein or soy exposure was reported in two of the six genetically modified mouse studies (Jin and MacDonald, 2002;Yang et al, 2003).…”
Section: Micementioning
confidence: 99%